2020
DOI: 10.3389/fcimb.2020.00317
|View full text |Cite
|
Sign up to set email alerts
|

ACE2, Much More Than Just a Receptor for SARS-COV-2

Abstract: The rapidly evolving pandemic of severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection worldwide cost many lives. The angiotensin converting enzyme-2 (ACE-2) has been identified as the receptor for the SARS-CoV-2 viral entry. As such, it is now receiving renewed attention as a potential target for anti-viral therapeutics. We review the physiological functions of ACE2 in the cardiovascular system and the lungs, and how the activation of ACE2/MAS/G protein coupled receptor contributes in reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
286
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 328 publications
(316 citation statements)
references
References 88 publications
(111 reference statements)
1
286
0
5
Order By: Relevance
“…This process leads to shedding of host ACE2 receptor and the loss of ACE2 function [22]. Because ACE2 counterbalances the deleterious effect of the RAAS, through effect of Angiotensin [1][2][3][4][5][6][7]36,37], the loss of ACE2 function amplifies the deleterious effect of angiotensin II (Ang II). It has been shown that Ang II stimulation leads to increased platelet size and activation, and that aspirin does not prevent such activation [16,38].…”
Section: Discussionmentioning
confidence: 99%
“…This process leads to shedding of host ACE2 receptor and the loss of ACE2 function [22]. Because ACE2 counterbalances the deleterious effect of the RAAS, through effect of Angiotensin [1][2][3][4][5][6][7]36,37], the loss of ACE2 function amplifies the deleterious effect of angiotensin II (Ang II). It has been shown that Ang II stimulation leads to increased platelet size and activation, and that aspirin does not prevent such activation [16,38].…”
Section: Discussionmentioning
confidence: 99%
“…The S protein, thus, loses its partners to enter the host cell, as illustrated on the right side of Figure 4 . ACE2 can be a target for inhibiting the entry of SARS-CoV-2 into the host cell because the binding affinity of the S protein of SARS-CoV-2 to the ACE2 receptor is 10–20-fold stronger than that of the S protein of SARS-CoV [ 68 , 69 , 70 ].…”
Section: Angiotensin-converting Enzyme 2 (Ace2)mentioning
confidence: 99%
“…Downregulation of ACE2 and elevated plasma angiotensin II level have been observed after SARS-CoV, SARS-CoV-2 or influenza infection, contributing to hyper-activated RAS cascades and ARDS [18][19][20]22,52 . Supplementing soluble ACE2 can balance RAS and improve ARDS conditions 17,[21][22][23]52,53 . These factors all seem to support the beneficial effects of the biological function of ACE2 for treating COVID-19 patients even though further studies are still needed to confer this advantage.…”
Section: Several Engineered Ace2 Proteins Bearing Different Number Ofmentioning
confidence: 99%